Taxonomy of the genus Atherigona Rondani (Diptera: Muscidae) from Korea - Suh, Sang Jae; Kwon, Yong Jung (Entomological research, 2018)
The Korean shoot fly genus Atherigona Rondani is reviewed taxonomically. A total of five species was identified: A. ( Acritochaeta ) orientalis Schiner , A. ( Atherigona ) biseta Karl, A. ( Atherigona ) falcata (Thomson), A. ( Atherigona ) oryzae Malloch, and A. ( Atherigona ) bifurca sp. nov. Of these, A. ( Atherigona ) bifurca sp. nov. is new to science, and A. ( Atherigona ) biseta Karl and A. ( Atherigona ) falcata (Thomson) are reported for the first time in Korea. A key to Korean species and photographs of external features are provided.